The forgiveness of blood - Heiblum, Leonardo 1970-; Lieberman, Jacobo 1970- (The Criterion collection, 2012)
In northern Albania a teenage brother and sister are physically and emotionally trapped in a cycle of violence, a result of their father's entanglement with a rival clan over a piece of land